Geopolitical Shocks and Commodity Market Dynamics - V, Vinoth Balaji; P S, Rajeswari; M, Sriram (International Journal of Accounting and Economics Studies, 2025)
This research comprehensively examines the effects of geopolitical risk (GPR) on global commodity markets and consolidates evidence ‎from 17 high-quality empirical studies published between 2010 and 2025. The SLR examines five thematic areas about geopolitical risk: (A) ‎a measurement of geopolitical risk, (B) the sensitivity of oil and energy markets, (C) Instability in agricultural and metal commodities, (D) ‎dynamics of safe-haven assets, and (E) the evolution of forecasting and modelling. The investigation critically examines how GPR ‎disruptions affect commodity markets. The literature establishes that geopolitical circumstances potentiate market space, redirect investment ‎flows, and create volatility in trade flows. The study recommends allowing for localised risk indices, integrated modelling architecture, and ‎cross-commodity portfolio analysis‎.